Relationship of Personal Hygiene and Nutritional Status to Intestinal Parasitic Infection in Simo, Boyolali - Sherlina Rintik Tirta Ayu; Sri Haryati; Yulia Sari; Sutartinah Handayani (Journal of Biodiversity and Biotechnology, 2021)
Intestinal parasitic infections are caused by protozoa, STH and non-STH worms. Immunity, which can be determined by measuring nutritional status, and personal hygiene can affect the occurrence of intestinal parasite infections. This study aims to determine the relationship between personal hygiene and nutritional status against intestinal parasite infections in elementary school students in Simo Boyolali. This type of analytic observational research with a cross sectional approach. Total sampling was taken at elementary school of Wates, Talakbroto 1, and Kedunglengkong 1 Simo, Boyolali. There were 11 students with worms infections, 16 with protozoa infections, and 4 with worms and protozoa infection. There was a relationship between washing hands before eating (p = 0.004), after eating (0.027), after defecating (p = 0.04), biting nails (p = 0.008), wearing footwear when leaving the house (p = 0.008) , removing shoes while playing during school breaks (p = 0.001), and nutritional status (p = 0.002) with intestinal parasite infection. There was no relationship between nail clipping once a week (p = 0.118) and the availability of a latrine (p = 0.416) with intestinal parasitic infections. So, there is a relationship between personal hygiene (washing hands before eating, after eating, after defecating, biting nails, wearing footwear when leaving the house, removing shoes when playing during school breaks, and nutritional status) and intestinal parasitic infections. Keywords: elementary school; protozoa; worms.